Penerapan Flipbook Berbasis PjBL untuk Meningkatkan Sikap Penalaran Kritis dan Kemampuan Menyimak Teks Narasi Kelas VI - Ananta, Siti Fatia; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
The low levels of critical reasoning attitudes and listening comprehension of narrative texts among sixth-grade students at SD Negeri 7 Boja, as evidenced by their Learning Objective Mastery Criterion (KKTP) scores falling below the target of 70, hinder both content understanding and the development of higher-order thinking skills. This study aimed to determine the effectiveness and impact of implementing a flipbook-based Project-Based Learning (PjBL) model on improving students’ critical reasoning attitudes and narrative listening skills. A mixed-methods approach with an embedded design was employed, involving 30 sixth-grade students as participants. Quantitative data were collected through listening comprehension tests and critical reasoning attitude questionnaires, while qualitative data were obtained through observations and interviews; these were then analyzed using descriptive statistics combined with thematic analysis. Quantitative findings indicated a significant increase in both variables, as reflected in the rise of the mean narrative listening score from 61.5 before the intervention to 82.3 afterward, as well as an improvement in critical reasoning attitude scores, with 86.7% of students achieving the “Good” to “Very Good” categories and surpassing the KKTP benchmark of 70. Qualitative analysis reinforced these results by showing that the PjBL-based flipbook fostered more interactive and authentic learning and encouraged students to actively construct projects that required critical analysis. It is concluded that the implementation of a PjBL-based flipbook is highly effective in enhancing critical reasoning attitudes and narrative listening skills among sixth-grade students at SD Negeri 7 Boja. The findings underscore the importance of utilizing PjBL models supported by interactive digital media as a key alternative for improving the quality of Bahasa Indonesia instruction and for developing twenty-first-century skills related to literacy and critical thinking.